Radiolysis as a source of 13C depleted natural gases in the geosphere. (December 2019) - Silva, Renzo C.; Snowdon, Lloyd R.; Huang, Haiping; Nightingale, Michael; Becker, Veith; Taylor, Stephen; Mayer, Bernhard; Pedersen, Jon H.; di Primio, Rolando; Larter, Steve
Highlights: Gamma radiolysis of crude oil generates natural gas. Radiolytic natural gas is wet and 13 C depleted. Organic-rich shales may be a ubiquitous source of radiolytic natural gas. Abstract: Is natural radioactivity a significant agent of hydrocarbon gas generation from sedimentary organic matter? Laboratory gamma radiation of dead crude oil (no solution gas) yields wet hydrocarbon gases depleted in 13 C: δ 13 C CH4 (−75‰ to −65‰), δ 13 C C2 H6 (−52‰ to −45‰), δ 13 C C3 H8 (−42‰ to −37‰) and δ 13 C n -C4 H10 (−35‰ to −32‰). Although laboratory irradiation dose rates are orders of magnitude higher than those in geological settings, radiolytic transformations occur at total radiation doses equivalent to those in natural geological settings over many millions of years. Radiolysis generates wet gases with isotopic signatures that might be interpreted as "biogenic" if only the methane carbon isotope ratio is considered. We examine situations where such gases may be quantitatively significant.